Capacity Building with Human Resource Development, Strengthening Organizations, and Institutional Reform to Achieve Cooperative Success in Sukabumi During the COVID-19 Pandemic - Ruswandi, Wawan; Patandung, Heri (KnE Social Sciences, 2022)
The government of Indonesia, through the Cooperative Recovery Section and Small and Medium Enterprises, continued to carry out its policies during the COVID-19 pandemic, one of which was increasing the quality, health, independence, and resilience of modern cooperatives in the community. However, to realize this, all parties are required to work together for increasing existing resources to further increase the success of cooperatives. One way to do that is to implement a capacity-building strategy, which is a series of strategies aimed at increasing organizational success that is efficient, effective, and responsive. This research determines the effect of capacity building on the success of cooperatives in the city of Sukabumi. The method used was causality associative analysis, and the population was cooperatives in the Sukabumi area. Data were analyzed using the covariance-based SEM analysis. Keywords: human resources development, organizational strengthening, institutional reform, cooperative success